2020
DOI: 10.1002/osp4.468
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use is negatively associated with body mass index: An observational study of electronic medical records

Abstract: Objective: Vaping is advertised as a method to mitigate weight gain after smoking cessation; however, while there is an established inverse association between conventional tobacco use and body mass index (BMI), there is little research on the relationship between e-cigarettes and BMI. This research tested whether e-cigarette use was associated with BMI. Methods:A secondary data analysis of 207,117 electronic medical records from the UAB was conducted. Patient data from 1 September 2017 through 1 June 2018 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Also, we found that E-cigarette is associated with high BMI in male individuals. Another study shows that E-cigarettes are associated with a lower BMI [25].…”
Section: Discussionmentioning
confidence: 96%
“…Also, we found that E-cigarette is associated with high BMI in male individuals. Another study shows that E-cigarettes are associated with a lower BMI [25].…”
Section: Discussionmentioning
confidence: 96%
“…However, further longitudinal studies were recommended 37 . On the other hand, another study linked e-cigarette use to a lower BMI 38 . Considering the different types of tobacco smoking, the long duration of smoking, and Palestinians' heavy tobacco use, more studies are needed to determine the health effects of e-cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings, however, were against the association between obesity and e-cigarettes use. Hoover et al [19] did not find a statistically significant risk of obesity in e-cigarettes users despite a higher risk of food addiction (RR = 2.71, 99%CI: 1.75-4.21, p < 0.001) [19], while Alqahtani et al [20] found that e-cigarettes use was associated with a lower BMI (B = −3.07, p = 0.021) [20].…”
Section: Obesitymentioning
confidence: 95%
“…We found six studies investigating a possible link between e-cigarettes and BMI and/or obesity [13,15,[17][18][19][20], while three more studies provided data regarding the attainment of obesity prevention recommendations in e-cigarettes smokers [21], e-cigarettes use due to weight control purposes [22], and preferred e-cigarettes flavors in obese people [23]. The largest studied population was reported by Zhao et al [17] on two cross-sectional data sets, including a total of 373,781 subjects (2015-2016: 189,306 individuals and 2018-2019: 184,475 persons), among whom 0.93% were past 30-day e-cigarettes users (2015-2016: 0.91% and 2018-2019: 0.96%).…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation